Existentialist Feminism in Etaf Rum’s A Woman is No Man - Dedi, Dania; Farlina, Nina (UIN Syarif Hidayatullah Jakarta, 2023)
This research aims to provide a qualitative study into existentialist feminism in Etaf Rum's novel A Woman is No Man (2019). The writers examine Arab American women from a three-generation family who emigrated from Palestine to America, which affected them in determining their meaning of existence under Arab American patriarchal culture: Fareeda as the first generation, Isra and Sarah as the second generation, and Deya as the third generation. This research used Simone de Beauvoir’s existentialist feminism theory. The findings show two out of the four Arab American women refused to break out from the Arab patriarchal culture, while the other two achieved their transcendence. The existence of Arab American women in the novel is not fully achieved based on Beauvoir’s idea of claiming their transcendence. In conclusion, the four Arab American female characters were influenced by generational differences when they were exposed to Arab culture in Palestine. Fareeda and Isra have more anti-assimilation toward American culture than Sarah and Deya, born in America. Sarah and Deya find meaning in their existence because they achieve their transcendence by becoming what they want to be, namely, working and independent women. Meanwhile, Fareeda and Isra find meaning in their existence in the realm of the patriarchal culture, which defines them as the Other since neither of them has ambitions for themselves but has always strived to submit to the Arab culture. Thus, Fareeda and Isra defined their meaning in existence as being mothers and wives.